2015
DOI: 10.1074/jbc.m115.649632
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Anatomy of ParA-ParA and ParA-ParB Interactions during Plasmid Partitioning

Abstract: Background: Small homodimeric ␦ 2 (ParA) and 2 (ParB) and parS mediate pSM19035 partitioning. Results: The ␦ 2 ATPase is a modular protein. Conclusion: ␦ 2 ⅐␦ 2 and ␦ 2 ⅐ 2 interacting domains are juxtaposed. Significance: ATP, nonspecific DNA, and 2 bound to parS induce multiple transitions on ␦ 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 42 publications
2
35
0
Order By: Relevance
“…4A). The formation of the ParB-ParA complex buries ∼450 Å 2 of protein surface from solvent, consistent with data indicating that the ParA-ParB interaction is weak (Vecchiarelli et al 2010;Volante and Alonso 2015). Strikingly, the ParB helices interact specifically with the ParA subunit arrangement found in the nucleotide sandwich dimer state; comparison of the ParA-ParB and ParA-DNA structures shows that ParB cannot dock in the dimer interface of the conformation that ParA adopts when bound to DNA without clash (Fig.…”
Section: Resultssupporting
confidence: 68%
See 4 more Smart Citations
“…4A). The formation of the ParB-ParA complex buries ∼450 Å 2 of protein surface from solvent, consistent with data indicating that the ParA-ParB interaction is weak (Vecchiarelli et al 2010;Volante and Alonso 2015). Strikingly, the ParB helices interact specifically with the ParA subunit arrangement found in the nucleotide sandwich dimer state; comparison of the ParA-ParB and ParA-DNA structures shows that ParB cannot dock in the dimer interface of the conformation that ParA adopts when bound to DNA without clash (Fig.…”
Section: Resultssupporting
confidence: 68%
“…Previous biochemical studies identified regions in ParB proteins that are involved in binding to their partner ParA proteins (Bartosik et al 2014;Volante and Alonso 2015). Work by Volante and Alonso (2015) revealed that pSM19035 plasmid ParB (also called ω) interacts with residues 88-119 in its partner, ParA (also called δ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations